Embryonic and larval development of pacific cod Gadus macrocephalus from the Tauyskaya Bay (northern Okhotsk Sea) - Ravil R. Yusupov (Известия ТИНРО, 2015)
Early embryogenesis and post-embryonic development of pacific cod Gadus macrocephalus Tilesius from the Tauyskaya Bay is investigated in experiment. Its fertilized eggs at stage II had the diameter 1.000-1.250 mm, on average 1.103 ± 0.003 mm. Numerous teardrop-shaped inclusions were observed in plasma of the blastodisk and in the blastomeres, presumably important for prevention of the eggs freezing under low temperature during incubation in vivo . Duration of the embryogenesis in vitro under the temperature 2.2 and 5.2оC was 490 and 768 hours, respectively. The prelarvae hatched at the length 4.28-5.10 mm, on average 4.34 ± 0.03 mm, and turned to mixed and exogenous feeding in 6 and 10 days, at the mean length 4.97 and 5.18 mm, respectively.